Process of work and production of care in caps: A case report (Research, Society and Development, 2021)
This article is an account of experience of organization of the work process in a Psychosocial Care Center of the Southern region of Brazil, analyzed using the methodology of the Flowchart Descriptor. The main objective is to publicly share the strategies built for the organization of the service and the production of mental health care. It was observed a great systematization of the work process, which prioritizes the spontaneous demands of new patients or those who already have Singular Therapeutic Projects in the service, including especially situations of crisis and urgency in mental health.